Promotion of macrophage activation by Tie2 in the context of the inflamed synovia of rheumatoid arthritis and psoriatic arthritis patients. (4th August 2019) - Kabala, Pawel A; Malvar-Fernández, Beatriz; Lopes, Ana P; Carvalheiro, Tiago; Hartgring, Sarita A Y; Tang, Man Wai; Conde, Carmen; Baeten, Dominique L; Sleeman, Matthew; Tak, Paul P; Connor, Jane; Radstake, Timothy R; et al.
Abstract: Objective: To examine the role of Tie2 signalling in macrophage activation within the context of the inflammatory synovial microenvironment present in patients with RA and PsA. Methods: Clinical responses and macrophage function were examined in wild-type and Tie2-overexpressing (Tie2-TG) mice in the K/BxN serum transfer model of arthritis. Macrophages derived from peripheral blood monocytes from healthy donors, RA and PsA patients, and RA and PsA synovial tissue explants were stimulated with TNF (10 ng/ml), angiopoietin (Ang)-1 or Ang-2 (200 ng/ml), or incubated with an anti-Ang2 neutralizing antibody. mRNA and protein expression of inflammatory mediators was analysed by quantitative PCR, ELISA and Luminex. Results: Tie2-TG mice displayed more clinically severe arthritis than wild-type mice, accompanied by enhanced joint expression of IL6, IL12B, NOS2, CCL2 and CXCL10, and activation of bone marrow-derived macrophages in response to Ang-2 stimulation. Ang-1 and Ang-2 significantly enhanced TNF-induced expression of pro-inflammatory cytokines and chemokines in macrophages from healthy donors differentiated with RA and PsA SF and peripheral blood-derived macrophages from RA and PsA patients. Both Ang-1 and Ang-2 induced the production of IL-6, IL-12p40, IL-8 and CCL-3 in synovial tissue explants of RA and PsA patients, and Ang-2 neutralization suppressed the production of IL-6 and IL-8 in the synovial tissue of RA patients. Conclusion: Tie2 signalling enhances TNF-dependent activation of macrophages within the context of ongoing synovial inflammation in RA and PsA, and neutralization of Tie2 ligands might be a promising therapeutic target in the treatment of these diseases.